THE REGENERATION EFFECT OF QUANTUM OPTICAL EFFECTS IN ANALOG SUPERCONDUCTING SYSTEMS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2019)
By longitudinal combination of two superconducting resonators, we realise a superconducting circulus analogue to the generic Hamilton cavity-optomechanical, which are of a different order of dimension. Longitudinal connections are achieved by incorporating a superconducting quantum interference into a high frequency resonator, so that the frequency of its resonance depends upon the zero-point current fluctuations of the nearby low frequency LC resonator. By using sideband drive fields the intrinsic coupling power is increased by controlling the amplitude of the drive field by around 15 kHz to 280 kHz. Our findings pave the way for the examination in a completely superconducting platform of optomechanical effects and allow quantum optical experiments with radiofrequencybands in which photons are unexplored. We consider a design for a cyclic microrefrigerator using a superconducting flux qubit. Adiabatic flux modulation and thermalisation can be used to transfer energy from the standard thin film resistance of the lower temperature to another at a higher temperature. Include the hot resistor as part of the highfrequency LC resonator and the cold as part of the low frequency oscilator while keeping both circuits under the damped mode, which enhance Photonic heat conduction's frequency selection. In an experimentally practical context we talk about the output of the computer. The complementarity of information and Thermodynamic Entropy is shown by this system as quantic bit erasure directly relates to resistance cooling.